2016
DOI: 10.1371/journal.pone.0161033
|View full text |Cite
|
Sign up to set email alerts
|

High-Iron Consumption Impairs Growth and Causes Copper-Deficiency Anemia in Weanling Sprague-Dawley Rats

Abstract: Iron-copper interactions were described decades ago; however, molecular mechanisms linking the two essential minerals remain largely undefined. Investigations in humans and other mammals noted that copper levels increase in the intestinal mucosa, liver and blood during iron deficiency, tissues all important for iron homeostasis. The current study was undertaken to test the hypothesis that dietary copper influences iron homeostasis during iron deficiency and iron overload. We thus fed weanling, male Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 49 publications
4
46
0
2
Order By: Relevance
“…Our results showed that rats receiving the low-iron diet for 14 days reached a hemoglobin concentration of 5.0 g/dL, and also had a significantly lower body weight (p < 0.05) than the normal rats (87.0 g vs 101.9 g). These observations are consistent with the report by Ha et al [17], confirming that the rats receiving the low-iron diet achieved iron-deficiency anemia after the acclimation period.…”
Section: Acclimation and Iron-deficiency Anemiasupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that rats receiving the low-iron diet for 14 days reached a hemoglobin concentration of 5.0 g/dL, and also had a significantly lower body weight (p < 0.05) than the normal rats (87.0 g vs 101.9 g). These observations are consistent with the report by Ha et al [17], confirming that the rats receiving the low-iron diet achieved iron-deficiency anemia after the acclimation period.…”
Section: Acclimation and Iron-deficiency Anemiasupporting
confidence: 93%
“…. As in the study by Ha et al [17], anemic rats remaining on the low-iron diet during the feeding trial gained weight at a slower rate (smaller weekly percent increases) compared to normal rats on the regular diet. However, anemic rats switched to the regular diet were able to gain weight essentially at the same rate as normal rats with or without FOS (Figure 1).…”
Section: Weight Gain and Water Intakementioning
confidence: 60%
See 1 more Smart Citation
“…For example, immunoreactive CP was reported to be decreased in hereditary hemochromatosis (HH), a genetic iron-loading disorder (67). Additional recent investigations in rats (112) and mice (110) demonstrated that high-iron intake can lead to copper depletion. In these studies, high-iron fed rodents developed severe copper deficiency-related pathologies, including growth retardation, cardiac hypertrophy, anemia, and impaired production of the liver-derived circulating FOX CP, which is a biomarker of moderate to severe copper deficiency (110, 112).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinementioning
confidence: 98%
“…Additional recent investigations in rats (112) and mice (110) demonstrated that high-iron intake can lead to copper depletion. In these studies, high-iron fed rodents developed severe copper deficiency-related pathologies, including growth retardation, cardiac hypertrophy, anemia, and impaired production of the liver-derived circulating FOX CP, which is a biomarker of moderate to severe copper deficiency (110, 112). Increasing dietary Cu prevented the development of these pathologies in rats, proving that copper deficiency was the underlying cause (112).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinementioning
confidence: 98%